Key performance evaluation of commercialized multiplex rRT-PCR kits for respiratory viruses: implications for application and optimization - Wanyu Feng; Yuqing Chen; Yanxi Han; Zhenli Diao; Zihong Zhao; Yuanfeng Zhang; Tao Huang; Yu Ma; Ziqiang Li; Jian Jiang; Jing Li; Jinming Li; et al. (Microbiology Spectrum)
ABSTRACT Respiratory tract infections (RTIs) caused by viruses are prevalent and significant conditions in clinical settings. Accurate and effective detection is of paramount importance in the diagnosis, treatment, and prevention of viral RTIs. With technological advancements, multiplex real-time reverse transcription polymerase chain reaction (rRT-PCR) assays have been developed and extensively adopted for the diagnosis of viral RTIs. Given the potential challenges in the detection performance of multiplex assays, this study evaluated the analytical sensitivity and competitive interference of the six most commonly used multiplex rRT-PCR kits for detection of respiratory viruses in China. The results revealed that the limits of detection were variable across the viruses and kits. Most of the evaluated multiplex kits demonstrated comparable or enhanced analytical sensitivity compared with singleplex kits for clinically significant viruses, including human adenovirus (HAdV)-3, HAdV-7, Omicron BA.5, H1N1pdm09, H3N2, B/Victoria, respiratory syncytial virus subtype A, and respiratory syncytial virus subtype B, whereas multiplex kits showed relatively less analytical sensitivity for human rhinovirus-B72, human metapneumovirus-A2, parainfluenza virus (PIV)-1, and PIV-3. In addition, most multiplex kits successfully identified co-infections when one analyte was present at a low concentration and another analyte was present at a high concentration.IMPORTANCEThe complexity and severity of viral respiratory tract infections (RTIs) emphasize the pivotal role of precise diagnosis for viral RTIs in guiding effective public health responses and ensuring appropriate medical interventions, given the substantial population at risk. This study highlights the necessity and importance of evaluating the analytical validity of multiplex real-time reverse transcription polymerase chain reaction assays, offering valuable insights into their optimization and application.